Fetal Cardiac Interventions - Shi-Min Yuan (Pediatrics and Neonatology)
The present article aims to highlight fetal cardiac interventions (FCIs) in terms of indications, strategies, and fetal prognoses. FCIs of the early years were predominantly pharmacological therapies for fetal arrhythmia or heart block. A transplacental transmission of therapeutic agents has now become the main route of pharmacological FCIs. There have been various FCI strategies, which can be categorized into three types: pharmacological, open FCIs, and closed FCIs. Rather than as a routine management for materno-fetal cardiac disorders, however, FCIs are only applied in those fetal cardiac disorders that are at an increased risk of mortality and morbidity and warrant an interventional therapy. Pharmacological FCIs have been well applied in fetal arrhythmias but require further investigations for novel therapeutic agents. The development of open FCI in humans is an issue for the long run. Closed FCIs may largely rely on advanced imaging techniques. Hybrid FCIs might be the future goal in the treatment of fetal heart diseases.